2007
DOI: 10.1002/ajmg.a.31679
|View full text |Cite
|
Sign up to set email alerts
|

Skewed X‐chromosome inactivation is associated with primary but not secondary ovarian failure

Abstract: Premature ovarian failure (POF) is the occurrence of menopause before the age of 40, and may present with either primary or secondary amenorrhea. Numerous cases of POF in women with X-chromosome deletions or translocations have been reported; thus, it is possible that smaller rearrangements undetectable by conventional cytogenetics may contribute to POF in some patients. In females with an abnormal X chromosome, cells with inactivation of the normal X may be selected against, causing skewed X-chromosome inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
2
7
0
1
Order By: Relevance
“…This leads to several diseases, including the fragile X syndrome (9,28). Skewed XCI has been previously related to POI (28,29). We have also found that this phenomenon is more frequent in women with POI, including patients with extreme XCI (>90%).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This leads to several diseases, including the fragile X syndrome (9,28). Skewed XCI has been previously related to POI (28,29). We have also found that this phenomenon is more frequent in women with POI, including patients with extreme XCI (>90%).…”
Section: Discussionsupporting
confidence: 64%
“…However, skewed XCI (>70%) can arise owing to alterations on the X chromosome. This leads to several diseases, including the fragile X syndrome (9,28). Skewed XCI has been previously related to POI (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the pattern of XCI is relatively constant across populations (see [10], [11], [12], [13], [14], [15] and Table 1) and ethnic differences are unlikely to explain the strong differences we observe.…”
Section: Resultsmentioning
confidence: 70%
“…Recently, several studies were performed to assess whether XCI might be a relevant factor in idiopathic POF development, whereas Sato et al 2006 observed more extremely skewed XCI in 43 women with POF, Bione et al 2006, Bretherick et al 2007, and Yoon et al 2008 failed to find any significant differences in the degree and frequency of skewed XCI in extended POF cohorts (59–151 women with POF). Therefore, an association between XCI and idiopathic POF seems unlikely.…”
Section: Introductionmentioning
confidence: 99%